2007
DOI: 10.1016/j.mcn.2007.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Gephyrin clustering is required for the stability of GABAergic synapses

Abstract: Although gephyrin is an important postsynaptic scaffolding protein at GABAergic synapses, the role of gephyrin for GABAergic synapse formation and/or maintenance is still under debate. We report here that knocking down gephyrin expression with small hairpin RNAs (shRNAs) in cultured hippocampal pyramidal cells decreased both the number of gephyrin and GABA(A) receptor clusters. Similar results were obtained by disrupting the clustering of endogenous gephyrin by overexpressing a gephyrin-EGFP fusion protein tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
115
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(129 citation statements)
references
References 56 publications
11
115
0
2
Order By: Relevance
“…We favor the first explanation, because the decreased density of synaptic ␥2-GABA A R clusters after knocking down septin 11 with shRNAs was not accompanied by parallel changes in the density of PSD-95 clusters or vGlut1 puncta. Moreover, we and others have shown that in these hippocampal cultures, interfering with the postsynaptic clustering of GABA A Rs or gephyrin in the postsynaptic cells leads to decreased GABAergic innervation of these cells (27,31,65). Therefore, if septin 11 clusters are involved in the assembly and/or maintenance of the postsynaptic GABAergic complex, their disruption would lead to decreased GABAergic innervation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…We favor the first explanation, because the decreased density of synaptic ␥2-GABA A R clusters after knocking down septin 11 with shRNAs was not accompanied by parallel changes in the density of PSD-95 clusters or vGlut1 puncta. Moreover, we and others have shown that in these hippocampal cultures, interfering with the postsynaptic clustering of GABA A Rs or gephyrin in the postsynaptic cells leads to decreased GABAergic innervation of these cells (27,31,65). Therefore, if septin 11 clusters are involved in the assembly and/or maintenance of the postsynaptic GABAergic complex, their disruption would lead to decreased GABAergic innervation.…”
Section: Discussionmentioning
confidence: 79%
“…3A). A DNA oligonucleotide encoding both arms of the shRNA was annealed with the corresponding reverse DNA strand, and the double-stranded DNA was ligated between the BbsI and XbaI sites of mU6pro vector (30,31). The control shRNAs were generated by introducing three point mutations in the sense and antisense arms of the corresponding shRNA (supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Gephyrin and GABA A -R Targeting-Synaptic GABA A -Rs are thought to be first inserted to extrasynaptic membranes and then laterally diffused into postsynaptic sites, where they are stabilized by the scaffolding protein complex (40,50,67,68). Both knock-out and knockdown of gephyrin expression disrupted the clustering of a major subset of synaptic GABA A -Rs and resulted in decreased GABAergic neurotransmission (28,40,50,69,70).…”
Section: Discussionmentioning
confidence: 99%
“…Both knock-out and knockdown of gephyrin expression disrupted the clustering of a major subset of synaptic GABA A -Rs and resulted in decreased GABAergic neurotransmission (28,40,50,69,70). However, not all GABA A -R clusters are dependent on gephyrin (70,71).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation